Avaliação do potencial de aplicação de biochar para remoção de metais e bisfenol A em sistemas aquosos - Andrade, Minéia Aparecida de Moraes de (2018)
Biochar (BC) produced from residues of local crops can be used as an alternative adsorbent for trace metals removal from water and effluents. In this study, the efficiency of BC from sugarcane bagasse (SB) produced at different pyrolysis temperatures (300, 400, 500 and 600 °C) in removal of trace metals (Cd, Pb; Cu; Cr, Ni and Zn) and bisphenol A was assessed. In addition, a commercially activated carbon was also used for comparison purposes. All BC were characterised using Scanning Electron Microscopy (SEM), Fourier Transformation Infrared (FTIR) and pyrolysis coupled to Gas Chromatography with Mass Spectrometry (Py-GC-MS). The adsorption capacity of the BC was evaluated at different pH and mass. The BPA results showed that the biochar had the best pH performance of 5.74, with a maximum adsorption of 88.89%. Regarding the metal ions, the biochar presented the best performance between pH 4 – 5.5 and the adsorbent mass with highest removal was 0.5 g. The maximal adsorption (Cd (II) – 51.49%, Cr (III) – 74.34%, Cu (II) – 91.97%, Ni (II) – 47.08, Pb (II) – 96.02% and Zn (II) – 40.56%) was observed for BC produced at 500 °C, probably due to the higher porosity of the material and functional groups observed in SEM, FTIR and Py-GC-MS analyses. The pseudo-second order and the Freundlich models were better fitted to the experimental data for both BPA and metal ions. Biochar produced from pyrolysis of sugarcane bagasse is a promising adsorbent for the simultaneous removal of BPA and trace metals from aqueous solutions.